Risk of falls displayed by elderly patients cared for by a geriatric outpatient clinic - Fernandes, Maria das Graças Melo (2014)
This study aims to identify risk factors for falls among elderly patients cared for at an outpatient clinic and the association between such factors. It is a cross-sectional study with 120 elderly patients. Data was collected using an instrument which contained a sociodemographic and clinical evaluation and the FallRisk Score (FR). The data was analyzed using descriptive statistics and the chi-squared test. Results demonstrate that the occurrence of falls was elevated in: 73.4% of women; 61.2% of sedentary patients; 60.8% of those between 60 and 69 years of age; 55.8% of hypertensive patients and 41.22% of those taking one or two medications. Considering this information, we recommend that there be a reflection, especially from health services, on basic care regarding prevention and early identification of risk factors for falls, in order to minimize their elevated prevalence among elderly patients cared for at the outpatient clinic level.  doi: 10.5216/ree.v16i2.20542.